A SOCIOLINGUISTICS STUDY: STUDENTS’ MOTIVATION UPON ELT IN THE COASTAL AREA OF BINTAN ISLAND - Nana Raihana Askurny; Indah Pujiastuti Pujiastuti (Prasasti: Journal of Linguistics)
Students who live in the coastal area in Bintan Island, Kepulauan Riau province, are expected to have greater access to the knowledge and information, regarding they stay in the open boundaries, Malacca straits. This social-region circumstance should enabled them to be familiar with English. However, students in this area do not conform to the expectation.  This research utilizes qualitative design, where the determination of research question, subject, and design is based on the researcher. Researcher has taken more than a hundred of students, as the research subject who live and study in the coastal area, in Bintan Island. For data collection, questionnaire is arranged by adapting AMTB, Attitude Motivation Test Battery, by Gardner (2004). According to the data analysis, it describes that students have a sizeable motivation in learning English, whereas their capability is not equitable. This shape caused by two main factors, such as English teacher’s role, real-contextual teaching method, and lack of opportunity